(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article presents the peculiarities of professional training of teachers. The analysis of ways of formation of cognitive independence of future specialists. Defines the main pedagogical requirements to the formation of creative thinking, cognitive independence of the future teachers of the Ukrainian language.